Can we afford the Green New Deal? - Yeva Nersisyan; L. Randall Wray (Levy Economics Institute of Bard College, 2020)
In this policy brief, Yeva Nersisyan and Senior Scholar L. Randall Wray argue that assessing the "affordability" of the Green New Deal is a question of whether there are suitable and sufficient real resources than can be mobilized to implement this ambitious approach to climate policy. Only after a careful resource accounting can we address the question of whether taxes and other means might be needed to reduce private spending to avoid inflation as the Green New Deal is phased in. Nersisyan and Wray provide a first attempt at resource budgeting for the Green New Deal, weighing available resources - including potential excess capacity and resources that can be shifted away from existing production - against what will be needed to implement the major elements of this plan to fight climate change and ensure a just transition to a more sustainable economic model.
Keywords: 330